1990
DOI: 10.1039/c39900000387
|View full text |Cite
|
Sign up to set email alerts
|

Self-sensitized photopolymerization of pyrrole

Abstract: Polypyrrole has been photochemically deposited on different kinds of solid surfaces by illumination with sunlight; this has been interpreted as the consequence of a self-sensitited initiation process.The search for new conducting materials of a polymeric nature has led to numerous reports, especially dealing with electrochemical growth of such substances.1--3 Recently, two new methods for photo-sensitized polymerization of pyrrole using Ru(bpy)32+ and CuI(dp)*+ (5) (where bpy = bipyridine and dpp = 2,9-dipheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…The photopolymerization method is considered as a good alternative to electropolymerization for the preparation of conjugated polymers. For instance, polypyrrole has been photochemically synthesized with and without the metal photocatalyst. Since the early 1990s, Iyoda and Shimidzu carried out some preliminary works on the photochemical solution polymerization of thiophene derivatives, i.e., benzo­[ c ]­thiophene, oligothiophenes, and dithienothiophenes, in the presence of an electron acceptor, e.g., dinitrobenzene, CCl 4 . The authors envisioned that the step-growth propagation was driven by the successive coupling reactions of cation radical species, which were generated by the photoinduced electron transfer from the excited monomer to the electron acceptor. Furthermore, a series of water-soluble thiophene derivatives were polymerized with the addition of photocatalyst potassium dichromate .…”
Section: Light-regulated Systemsmentioning
confidence: 99%
“…The photopolymerization method is considered as a good alternative to electropolymerization for the preparation of conjugated polymers. For instance, polypyrrole has been photochemically synthesized with and without the metal photocatalyst. Since the early 1990s, Iyoda and Shimidzu carried out some preliminary works on the photochemical solution polymerization of thiophene derivatives, i.e., benzo­[ c ]­thiophene, oligothiophenes, and dithienothiophenes, in the presence of an electron acceptor, e.g., dinitrobenzene, CCl 4 . The authors envisioned that the step-growth propagation was driven by the successive coupling reactions of cation radical species, which were generated by the photoinduced electron transfer from the excited monomer to the electron acceptor. Furthermore, a series of water-soluble thiophene derivatives were polymerized with the addition of photocatalyst potassium dichromate .…”
Section: Light-regulated Systemsmentioning
confidence: 99%
“…A photoinitiating system isn't strictly needed to photopolymerize pyrrole. Studies by Rodríguez and González-Velasco (1990) have shown that pyrrole itself can be excited by UV irradiation to initiate photopolymerization. This self-sensitized polymerization technique however requires long irradiation times and produces a polymer with a low conductivity (Rodríguez and González-Velasco, 1990).…”
Section: Photosensitive Polypyrrole Formulationsmentioning
confidence: 99%
“…25,26 Previously, there were reports on the multiphotonsensitized polymerization of pyrrole, self-sensitized photopolymerization of pyrrole and photopolymerization of pyrrole using ruthenium complexes, cobalt complexes, and copper complexes as electron acceptors. 27,28 However, few reports on photopolymerization were found during a comprehensive literature survey.…”
Section: Introductionmentioning
confidence: 99%